Spitz tumour with ALK rearrangement: a case report and literature review - Lai, Shau-Kong; Bakrin, Ikmal Hisyam; Abd Rauf,, Nurhafidzah; Abdul Raub, Sayyidi Hamzi (Malaysian Society of Pathologists, 2024)
Spitz tumour with ALK rearrangement is a recently described entity and a rare tumour. The incidence of Spitz tumour was estimated at 3.63 per 100,000 persons in American paediatric population; while there is no data in Asian population. Here we reported a case of an eleven-year-old Asian boy who presented with a left shin nodule of two months’ duration. The skin biopsy revealed a Spitz tumour with predominantly spindle cell morphology arranged in fascicles, vertically orientated nests and radial growth pattern. Junctional component, melanin pigment or Kamino bodies were not identified. Immunohistochemical study displayed homogenous cytoplasmic staining for ALK. Fluorescence in-situ hybridisation (FISH) analysis confirmed ALK rearrangement. Review of the literatures demonstrated that positive ALK immunohistochemistry may not correlate with ALK rearrangement. ALK-rearranged Spitz tumour confirmed with FISH analysis favour clinically benign behaviour despite atypical histomorphology or positive sentinel lymph node. Therefore, correlation of histomorphology, immunohistochemical stain and molecular study are important for the definitive diagnosis of this entity.